1989
DOI: 10.1002/cber.19891220812
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Struktur von Lithiumkomplexen mit pentahapto‐gebundenen, substituierten Cyclopentadienylliganden

Abstract: Die Umsetzung von [Tris(trimethylsilyi)cyclopentadienyl]lithium, ~is(trimethylsilyl)yclopentadienyl]lithiumund (Di-tert-butylcyclopentadieny1)lithium mit Lewis-Basen (Ether, Amine, Thioether) fiihrt zu kristallinen, sehr luft-und feuchtigkeitsempfindlichen Addukten la-k, 221 thylsily1)cyclopentadienids konnte diese Vermutung durch eine Rontgenstrukturanalyse bestatigt werden: Diese Verbindung besitzt eine Polydecker-Sandwich-Struktur".Stickstoff-Basen-Addukte des [Tris(trimethylsilyl)cyclopentadienyl]lithiums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 13 publications
2
7
1
Order By: Relevance
“…The position of the lithium atom is almost perfectly perpendicularly to the Cp plane (177.4°), with a deviation of the Li–Cp cent line from the ring axis of only 2.6°. Compared to the Li–Cp cent distances in lithium pentaarylcyclopentadienide complexes ((thf)·Li­[C 5 ( p - t Bu-C 6 H 4 )]: 210.0 pm; (thf)·Li­[C 5 ( m -Me 2 C 6 H 3 )]: 209.4 pm), we found that it is significantly shorter in complex 1 but slightly longer than the distance found in a related tris­(trimethylsilyl)­cyclopentadienyl lithium complex ((thf)·Li­[C 5 H 2 (SiMe 3 ) 3 ]: 179.4–180.3 pm). The 1 H and 13 C NMR spectra of a C 6 D 6 solution of 1 ·OEt 2 (Figures S1–S3) show the expected resonances of the cyclopentadienyl ligand, with one resonance for the CH groups and two resonances for the CH 3 groups, due to slow rotation of the isopropyl groups and therefore one set of methyl groups facing toward the metal atom and one set facing away from the metal atom.…”
Section: Resultscontrasting
confidence: 50%
“…The position of the lithium atom is almost perfectly perpendicularly to the Cp plane (177.4°), with a deviation of the Li–Cp cent line from the ring axis of only 2.6°. Compared to the Li–Cp cent distances in lithium pentaarylcyclopentadienide complexes ((thf)·Li­[C 5 ( p - t Bu-C 6 H 4 )]: 210.0 pm; (thf)·Li­[C 5 ( m -Me 2 C 6 H 3 )]: 209.4 pm), we found that it is significantly shorter in complex 1 but slightly longer than the distance found in a related tris­(trimethylsilyl)­cyclopentadienyl lithium complex ((thf)·Li­[C 5 H 2 (SiMe 3 ) 3 ]: 179.4–180.3 pm). The 1 H and 13 C NMR spectra of a C 6 D 6 solution of 1 ·OEt 2 (Figures S1–S3) show the expected resonances of the cyclopentadienyl ligand, with one resonance for the CH groups and two resonances for the CH 3 groups, due to slow rotation of the isopropyl groups and therefore one set of methyl groups facing toward the metal atom and one set facing away from the metal atom.…”
Section: Resultscontrasting
confidence: 50%
“…Lithium 1,3‐bis(trimethylsilyl)cyclopentadienide63 reacts with 1 to exclusively give the complex pentamethylcyclopentadienyl[1,3‐bis(trimethylsilyl)cyclopentadienyl]silicon ( 4 ), whereas partial ligand redistribution is observed in the reaction of lithium 1,2,4‐trimethylcyclopentadienide64 leading to the silicocenes 5 , 6 , and 2 (see Scheme ) 62. The reaction with lithium cyclopentadienide was performed in a special “two chamber” NMR tube50 showing that the π‐complex cyclopentadienyl(pentamethylcyclopentadienyl)silicon ( 7 ) is quantitatively formed at −50 °C, but starts to decompose already at −30 °C 62…”
Section: Reactivity Of the [(π‐Me5c5)si]+ Cationmentioning
confidence: 99%
“…We have been examining the properties of 1,2,4-tris(trimethylsilyl)cyclopentadiene (HCp 3Si ) [12,13] as a sterically bulky ligand in s-block metal chemistry. [14,15] In conjunction with the previously reported structure of the substituted magnesocene [1,2,4- [16] a homologous series of unsolvated Group-2 metallocenes from Mg to Ba has now been synthesized and crystallographically authenticated.…”
Section: Introductionmentioning
confidence: 99%